A computational study of accelerating, steady and fading negative streamers in ambient air. (1st September 2022) - Guo, Baohong; Li, Xiaoran; Ebert, Ute; Teunissen, Jannis
Abstract: We study negative streamers in ambient air using a 2D axisymmetric fluid model. Depending on the background electric field, we observe accelerating, steady and fading negative streamers. Fading occurs in low background fields, when negative streamers lose their field enhancement and when their velocities become comparable to their maximal electron drift velocities. Our focus is on the steady propagation mode, during which streamer properties like radius and velocity hardly change. However, this mode is unstable, in the sense that a small change in conditions leads to acceleration or deceleration. We observe steady negative streamers in background fields ranging from 9.19 kV cm −1 to 15.75 kV cm −1, indicating that there is no unique steady propagation field (or stability field). Another finding is that steady negative streamers are able to keep propagating over tens of centimeters, with only a finite conductive length behind their heads, similar to steady positive streamers. Approximately linear relationships are observed between the optical diameter and properties like the streamer velocity and the streamer head potential. From these linear relations, we obtain rough lower bounds of about 0.27 mm to 0.35 mm for the minimal optical diameter of steady negative streamers. The lowest background field in which a steady negative streamer could be obtained is 9.19 kV cm −1 . In contrast, steady positive streamers have recently been obtained in a background field as low as 4.05 kV cm −1 . We find that the properties of steady negative and positive streamers differ significantly. For example, for steady negative streamers the ratio between streamer velocity and maximal electron drift velocity ranges from about 2 to 4.5, whereas for steady positive streamers this ratio ranges from about 0.05 to 0.26.